EDUKASI PEMANFAATAN DAUN JAMBU BIJI MERAH (Psidium guajava L.) SEBAGAI PENGENDALI KADAR GULA DARAH PADA PASIEN PROLANIS DADI WARAS DI PEDAN, KLATEN - Devina Ingrid; Atur Semartini; Eka Wisnu Kusuma (LPPM Institut Pendidikan Nusantara Global, 2026)
Management of diabetes mellitus (DM) requires patients to adopt healthy lifestyle habits to control blood glucose levels and prevent long-term complications. Red guava leaves contain polyphenolic compounds, particularly tannins, which possess astringent properties. These compounds can help regulate the rate of increase in blood glucose levels, preventing excessive spikes. An infusion prepared from red guava leaves (Psidium guajava L.) is beneficial for controlling blood glucose levels in patients with diabetes mellitus. This community service was preventive activity and aimed to reduce the adverse effects of inappropriate dietary patterns that may worsen the condition of patients with diabetes. The program targeted patients who are members of the Chronic Disease Management Program (Prolanis) Club Dadi Waras in Sobayan Village, Pedan District, Klaten Regency. The activity was conducted through health education sessions combined with a workshop on the preparation of red guava leaf (Psidium guajava L.) infusion. The large number of questions asked during the presentation demonstrated the participants' high level of enthusiasm. Furthermore, participants' knowledge increased between before and after the presentation, as evidenced by their improved ability to answer pre- and post-test questions.. Based on the paired samples t-test results, the significance value was < 0.05, indicating a significant effect of the educational intervention in this community service activity. This was evidenced by higher post test scores. Education on the utilization of natural ingredients represents a beneficial approach to controlling blood glucose levels and improving the overall health of patients with diabetes.